Novel hydroxyl carboximates derived from β-elemene: design, synthesis and anti-tumour activities evaluation. (31st December 2022) - Gao, Yuan; Mao, Nian-Dong; Che, Hao; Xu, Li; Bai, Renren; Wang, Li-Wei; Ye, Xiang-Yang; Xie, Tian
Abstract: A series of novel N -alkyl- N -hydroxyl carboximates derived from β -elemene were fortuitously discovered. Most of them showed more potent anti-proliferative activities than their lead compound β -elemene (1 ). Notably, compound 11i exhibited significant inhibitory effects on the proliferation of three lung cell lines (H1975, A549 and H460) and several other tumour cell lines (H1299, U87MG, MV4-11, and SU-DHL-2). Preliminary mechanistic studies revealed that compound 11i could significantly induce cell apoptosis. Further in vivo study in the H460 xenograft mouse model validated the anti-tumour activities of 11i with a greater tumour growth inhibition (TGI, 68.3%) than β -elemene and SAHA (50.1% and 55.9% respectively) at 60 mg/kg ip dosing, without obvious body weight loss and toxicity. Thus, such N -alkyl- N -hydroxyl carboximate class of compounds exemplified as 11i demonstrated potent anticancer activities both in vitro and in vivo, and should warrant further investigation for potential anticancer therapy. Graphical Abstract: UF0001